Uma abordagem para atestar a suportabilidade dielétrica a formas de onda não padronizadas nos ensaios de equipamentos de alta tensão - Wickert, Humberto Margel (2021)
The non-standard waveforms caused by high frequency transients pose a challenge when it comes to their representation in testing high-voltage equipment. Such a challenge is worrisome for electric power utilities and manufacturers of high voltage electrical equipment, since such transient voltages might not be represented by standard waveforms. The standard lightning impulse test 1.2/50 μs is important for factory testing of equipment and evaluating its performance before installation in the electrical system. However, actual surge waveforms are complex and difficult to reproduce in high voltage laboratories. The complexity of the resulting waves in the electrical system has increased in recent years, mainly due to systemic changes and integration of equipment with new technologies. With the different characteristics imposed on the equipment, evaluations of the tests currently used are necessary. In order to overcome this obstacle, this Thesis suggests a method that represents non-standard waveforms in equipment tests in a laboratory. Based on the multiresolution analysis of the wavelet transform, the method considers the equivalence of amplitude and entropy in the decomposition levels among the waveforms. For that purpose, alterations are suggested in the following lightning impulse parameters: amplitude, cut-off instant and front time. The results show that for most cases, the composition between a full atmospheric impulse waveform with cut atmospheric impulse waves at different instants is sufficient to represent the non-standard voltages. Only when the transient voltage spectral density falls predominantly in a frequency range above 3.125 MHz, will there be need for a complementary lightning impulse with a steep front time. By using this approach, it is not expected to describe exactly the rupture process of the diverse dielectrical media when subjected to non-standard waveforms. The aim is to bring together lightning impulse waveforms that have similar features to non-standard waveforms. Thus, the method’s application allows manufacturers and power utilities to subject the equipment to conditions that properly represent the transient effects, through lightning impulse tests carried out at high voltage laboratories.